A Survey on Oscillation of Impulsive Ordinary Differential Equations. (14th April 2010) - Agarwal, Ravi P.; Karakoç, Fatma; Zafer, Ağacık
Abstract : This paper summarizes a series of results on the oscillation of impulsive ordinary differential equations. We consider linear, half-linear, super-half-linear, and nonlinear equations. Several oscillation criteria are given. The Sturmian comparison theory for linear and half linear equations is also included.